Penguatan Keterampilan Membaca Al-Qur’an dan Pembentukan Karakter Religius Moderat melalui Metode Ummi di Sma Wahas Maduran - Fahimah, Siti; Luthfiyah, Lujeng (PARTISIPATORY, 2025)
This community service program aims to enhance Quranic reading skills and foster a moderate religious character among Generation Z students at SMA Wahas Maduran through the Ummi Method. As part of Generation Z, high school students are accustomed to digital technology, which presents challenges in developing proper Quranic reading skills as well as maintaining a balanced and tolerant religious attitude. This program employs the Participatory Action Research (PAR) method, involving educators, students, and school stakeholders. Student mentoring and continuous evaluation are among the key actions taken. The results indicate that the Ummi Method, which is gradual and structured, effectively improves students’ ability to read the Quran with correct makhraj and tajwid. Additionally, this approach plays a significant role in fostering a moderate religious character, instilling tolerance, and helping students balance their religious practices in today’s digital era. The success of this program relies on ongoing evaluation, continuous guidance from teachers, and strong school support. Therefore, this initiative encourages the broader implementation of the Ummi Method in both formal and non-formal education, as it will help Generation Z address religious challenges in the modern millennial era